STRATEGI KESANTUNAN BERBAHASA MAHASISWA DALAM MENULIS PESAN SINGKAT KEPADA DOSEN MELALUI MEDIA WHATSAPP - Eka Wahyu, Gede (Berajah Journal, 2024)
This research aims to determine students' realization of language politeness when writing short messages via WhatsApp media. Data was taken from thirty students in the odd-even semester period 2022-2023. The data is a short message from students when asking the lecturer to validate the KRS and provide thesis guidance. The research design used in the research is a qualitative design with a pragmatic approach. The theory used as a research reference is the theory of language politeness and Indonesian imperative politeness. The results of data analysis show that the majority of students use negative politeness by implementing actions of apologizing and humbling themselves. Then students also use positive politeness by realizing acts of intimacy and focusing their attention on their speech partner. Only a few students use indirect politeness and direct politeness patterns.